Glapan Weir Irrigation System Optimization Strategy to Increase Agricultural Yield (Universitas Negeri Semarang, 2022)
This study aims to identify the constraints and problems that exist in the irrigation system and to develop an optimization strategy for the Glapan Dam irrigation system in Gubung District, Grobogan Regency. This type of research uses descriptive quantitative. The data collection technique in this study used a questionnaire distributed to key persons who had been determined by purposive sampling. The analysis used is Analytical Hierarchy Process (AHP) then processed using Expert Choice software. The results show that the obstacles and problems that are still faced in the management of the irrigation system in Glapan Weir are the sedimentations of the Tuntang River which causes a reduction in water supply, and the lack of availability of tools such as pumps, sluice gates, and water flow measuring devices. The most prioritized criteria in the strategy of optimizing the irrigation system in Glapan Dam to increase agricultural yields is the money criterion with a weight value of 0.520 and the first priority alternative in the irrigation system optimization strategy to increase agricultural yields is an alternative government fund with a weighted value of 0.211. Penelitian ini bertujuan untuk mengidentifikasi kendala dan permasalahan yang ada pada sistem irigasi serta menyusun strategi optimasi sistem irigasi Bendung Glapan di Kecamatan Gubung, Kabupaten Grobogan. Jenis penelitian ini menggunakan deskriptif kuantitatif. Teknik pengumpulan data dalam penelitian ini menggunakan kuesioner yang dibagikan kepada key person yang telah ditentukan secara purposive sampling. Analisis yang digunakan adalah Analytical Hierarchy Process (AHP) kemudian diolah menggunakan software Expert Choice. Hasil penelitian menunjukkan bahwa kendala dan permasalahan yang masih dihadapi dalam pengelolaan sistem irigasi di Bendung Glapan adalah sedimentasi Sungai Tuntang yang menyebabkan berkurangnya pasokan air, dan kurangnya ketersediaan alat seperti mesin pompa, pintu air, dan alat pengukur debit air. Kriteria yang paling diprioritaskan dalam strategi optimalisasi sistem irigasi di Bendung Glapan untuk meningkatkan hasil pertanian adalah kriteria uang dengan nilai bobot 0,520 dan alternatif prioritas pertama dalam strategi optimalisasi sistem irigasi untuk peningkatan hasil pertanian adalah alternatif dana pemerintah dengan nilai bobot 0,211.